The Voice of the Qur'an's Potential in Pain Management : Review Study - Iwan Purnawan; Yunita Widyastuti; Sri Setiyarini; Probosuseno Probosuseno (Jurnal Berita Ilmu Keperawatan, 2022)
Pain is multidimensional. Pharmacological therapy is still not optimal and has unwanted side effects. Therefore, a safe, effective, and comprehensive non-pharmacological therapy is needed to compensate for the lack of pharmacological therapy. Listening to the recitation of the Quran in several studies has been shown to have a relaxing effect in various situations. The study aims to see whether listening to the Quran as a type of non-pharmacological therapy will help people overcome pain. Method used is comprehensive search on multiple databases (Clinical Key, Cochrane Lab, Medline, Host EBSCO, ProQuest, Science Direct, and Springer Link) using the term "Quran, Holy Quran, Koran, Quran, Pain, Pain Management, and endorphins.". There were 209 articles found, and after several screening stages, 9 articles met the inclusion and exclusion criteria. The level of evidence and the Cochrane Collaboration's tool for assessing the risk of bias was used to assess the article's quality.  The result is listening to The Qur'an has been shown to reduce pain in post-surgery, blood sampling, wound care, dysmenorrhea, and childbirth. Some studies are still lacking evidence and are biased. Listening to the Quran is highly recommended for use as a health service.